Changes in energy availability across the season in Division I female soccer players - Reed, J. L.; de Souza, M. J.; Williams, N. I. (Journal of Sports Sciences, 2013)
Low energy availability [(energy intake - exercise expenditure)/kg lean body mass], a component of the Female Athlete Triad, has been associated with menstrual disturbances and low bone mass. No studies have examined the energy availability of athletes across a season. The purpose of this study was to assess the prevalence of, and what contributes to, low energy availability in Division I female soccer players across a season. Nineteen participants aged 18-21 years (mean VO2max: 57.0 ± 1.0 mL/kg.min) were studied during the pre, mid, and post season. Mean energy availability was overall lowest at mid season, and lower at mid than post season (35.2 ± 3.7 vs. 44.5 ± 3.7 kcal /kg lean body mass, P = 0.009). Low energy availability (<30 kcal · kg-1 lean body mass) was observed in 5/19 (26.3%), 5/15 (33.3%), and 2/17 (11.8%) of participants during the pre, mid, and post season. Dietary energy intake was lower mid (P = 0.008) and post season (P = 0.022) than it was pre season (pre: 2794 ± 233 kcal/day; mid: 2208 ± 156 kcal/day; post: 2161 ± 143 kcal/day). Exercise energy expenditure decreased significantly (P = 0.001) over time (pre: 819 ± 57 kcal/day; mid: 642 ± 26 kcal/day; post: 159 ± 28 kcal · day-1). Low energy availability was due to lower dietary energy intake at lunch during pre season (P = 0.014) and during lunch and dinner during mid season (P = 0.030). Energy availability was inversely related to body dissatisfaction (r = -0.62, P = 0.017) and drive for thinness (r = -0.55, P = 0.041) during mid season. Although most Division I female soccer players are not at risk for low energy availability, a concerning proportion exhibited low energy availability at pre or mid season. Further studies are needed to explore strategies to prevent and monitor low energy availability in these athletes.